2015
DOI: 10.5194/tc-9-1039-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ice-dynamic projections of the Greenland ice sheet in response to atmospheric and oceanic warming

Abstract: Abstract. Continuing global warming will have a strong impact on the Greenland ice sheet in the coming centuries. During the last decade (2000–2010), both increased melt-water runoff and enhanced ice discharge from calving glaciers have contributed 0.6 ± 0.1 mm yr−1 to global sea-level rise, with a relative contribution of 60 and 40% respectively. Here we use a higher-order ice flow model, spun up to present day, to simulate future ice volume changes driven by both atmospheric and oceanic temperature changes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 87 publications
8
136
2
Order By: Relevance
“…The consequent mass loss, of which ∼40 % is from ice discharge, contributes 0.62 mm year −1 to GMSL rise, similar to observations (section BGreenland Ice Sheet^), giving confidence in the ice sheet model. With forcing from an ensemble of ten CMIP5 AOGCMs under the four RCP scenarios, Fürst et al [104] found the contributions to GMSL rise by 2100 relative to 2000 range from 0.04±0.02 m (1 std. dev.)…”
Section: Greenland Ice Sheetmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequent mass loss, of which ∼40 % is from ice discharge, contributes 0.62 mm year −1 to GMSL rise, similar to observations (section BGreenland Ice Sheet^), giving confidence in the ice sheet model. With forcing from an ensemble of ten CMIP5 AOGCMs under the four RCP scenarios, Fürst et al [104] found the contributions to GMSL rise by 2100 relative to 2000 range from 0.04±0.02 m (1 std. dev.)…”
Section: Greenland Ice Sheetmentioning
confidence: 99%
“…Fürst et al [104] forced an ice sheet model that accounts for basal lubrication and ocean thermal forcing of ice discharge with reanalysis data over the period 2005-2010. The consequent mass loss, of which ∼40 % is from ice discharge, contributes 0.62 mm year −1 to GMSL rise, similar to observations (section BGreenland Ice Sheet^), giving confidence in the ice sheet model.…”
Section: Greenland Ice Sheetmentioning
confidence: 99%
“…Huybrechts, 1990;Letréguilly et al, 1991;Zweck and Huybrechts, 2005;Greve et al, 2011). For the GrIS the forcing record was created following Fürst et al (2015). We combine a synthesised Greenland δ 18 O record derived from Antarctica Dome C using a bipolar seesaw model (Barker et al, 2011) with the NEEM temperature reconstruction (NEEM community members, 2013) between 128.44 and 120 kyr BP.…”
Section: Simulations Of the Greenland And Antarctic Ice Sheetsmentioning
confidence: 99%
“…On average, the GrIS contributed to 0.47 ± 0.23 mm a −1 of sea-level rise from 1991 to 2015 (van den Broeke et al, 2016), with an accelerated rate of 0.89 ± 0.09 mm a −1 from 2010 to 2014 (Yi et al, 2015). In the future, the GrIS is expected to continue losing mass, contributing to a sea-level rise relative to the 20th century between 90 and 280 mm by 2100 in the worst-case scenario (RCP8.5) IPCC, 2013;Clark et al, 2015;Fürst et al, 2015). This accelerated ice loss is due to a combination of increased surface melting and enhanced ice discharge from marine-terminating glaciers to the ocean (van den .…”
Section: Introductionmentioning
confidence: 99%
“…Various numerical models have been used to simulate current submarine melt rates (Jenkins, 2011;Rignot et al, 2016;Sciascia et al, 2013;Xu et al, 2012Xu et al, , 2013 and dynamic retreat Vieli and Nick, 2011) of the GrIS marine-terminating glaciers, as well as ice-dynamic future projections of the whole GrIS (Fürst et al, 2015;Nowicki et al, 2013), due to changes in the oceanic temperatures. However, how this thermal forcing affected the past GrIS configuration has not been explored from a modelling perspective so far.…”
Section: Introductionmentioning
confidence: 99%